Comparative Aquatic Toxicity of Gold Nanoparticles and Ionic Gold Using a Species Sensitivity Distribution Approach. (11th October 2015) - Botha, Tarryn L.; James, Tanyn E.; Wepener, Victor
Abstract : Gold nanoparticles (nAu) are used in drug delivery systems allowing for targeted cellular distribution. The effects of increased use and release of nanoparticles into the environment are not well known. A species sensitivity distribution (SSD) allows for the ecotoxicological hazard assessment of a chemical based on single species toxicity tests. Aquatic toxicity needs to be related to particle characterization in order to understand the effects. The behaviour of nAu in the medium changed as the concentration increased. The toxic potential of ionic gold and nAu was expressed as a hazardous concentration where 5% of species will be harmed (HC5). The HC5 for nAu was much higher (42.78 mg/L) compared to the ionic gold (2.44 mg/L). The differences between the hazard potentials of nAu and ionic gold were attributed to the nAu not releasing any Au ions into solution during the exposures and following an aggregation theory response. Exposures to ionic gold on the other hand followed a clear dose dependent response based on the concentration of the ionic metal. Although SSDs present an indication of the relative hazard potential of nanoparticles, the true worth can only be achieved once other nanoparticle characteristics and their behavior in the environment are also considered.